External Morphology of the Immatures of Polybia paulista (Hymenoptera: Vespidae) - Solis, Daniel Russ; Dias, Nathalia Baptista [UNESP]; Paterson Fox, Eduardo Goncalves (Florida Entomological Soc, 2012)
The immatures of Polybia paulista Ihering were described using light and scanning electron microscopy and the results are compared with previous descriptions within the same or related wasps. This study is based on 2 whole nests collected in the municipality of Rio Claro, São Paulo, in Brazil. We have detected the existence of 5 larval instars. The main morphological alterations over development occur in the relative size of structures, yet certain structures appear with subsequent instars and become more evident later in development: increasing density in the number of body spines and papillae; the appearance of body setae in fifth-instar larvae; opening of spiracles upon second-instar larvae; 2 body shapes in fifth-instar larvae; the appearance of a lateral tooth on the mandibles of fourth instar; presence of spines on the maxillae of fifth-instar larvae; altered shape of galea and palps upon third-instar larvae from a cluster of sensilla to a conical elevation; and the appearance of spines on postmentum upon fourth-instar larvae. This way, the present study presents a detailed description of the immatures of P. paulista, and we hope the presented information can be useful to morphological, taxonomic, and phylogenetic studies.

Os imaturos de Polybia paulista Ihering foram descritos e comparados, com o auxílio da microscopia óptica e eletrônica de varredura. Foram analisados os imaturos provenientes de dois ninhos obtidos no município de Rio Claro, SP, Brasil. Verificou-se a existência de cinco instares larvais. Durante o desenvolvimento ocorrem principalmente mudanças no tamanho das estruturas. Além disso, certas estruturas surgem e se tornam evidentes com o desenvolvimento da larva: aumento da densidade de espinhos e papilas no corpo; presença de setas no corpo da larva de último instar; abertura dos espiráculos a partir do segundo instar; dois formatos de corpo na larva de último instar; a partir do quarto instar, a presença de dente lateral na mandíbula; presença de espinhos na maxila do último instar; mudança do formato da galea e palpos a partir do terceiro instar, de um agrupamento de sensilas para um cone; e o surgimento de espinhos na gula a partir do quarto instar. Desta maneira, o presente estudo efetuou uma caracterização detalhada dos imaturos de P. paulista, cujas informações poderão ser talvez úteis para estudos morfológicos, taxonômicos e filogenéticos.
Keywords: Larvae; Development; Polistinae; Epiponini; Myrapetra